Enhanced visible light photocatalytic degradation of rhodamine B using Ni1-xCaxFe2O4 (0 ≤ x ≤ 0.5) nanoparticles: Performance, kinetics and mechanism. (October 2022) - Sundararajan, M.; Bonisha, B.; Ubaidullah, Mohd; Shaikh, Shoyeb Mohamad F.; Revathi, S.; Thiripurasundari, D.; Dhiwahar, A. Tony; Pandit, Bidhan; Dash, Chandra Sekhar; Shahazad, Mohd
Highlights: Cost-efficient synthesis of Ni1-x Cax Fe2 O4 (0 ≤ x ≤ 0.5)) nanoparticle. The energy gap was calculated between 3.05 eV and 2.11 eV with calcium doping. The efficiency of photocatalyst increases Ca with doping. The PCD efficiency for NCF5 is 99.69% compared to NF1. Abstract: In this study we have synthesized calcium doped nickel ferrite (Ni1-x Cax Fe2 O4 (0 ≤ x ≤ 0.5)) nanoparticles by microwave combustion technique. The prepared nanoparticles and its degradation have been studied using one of the most harmful dye rhodamine B (RhB), by means of enhanced visible light photocatalytic degradation. The structural characteristics of the sample was analysed using XRD, FT-IR, HR-SEM, TEM and XPS. Those were utilised to observe the structure, vibrations and surface morphology of the calcium doped nickel ferrite sample. UV-DRS, PL and VSM studies, give optical and magnetic properties of obtained samples. From XRD the crystallite size obtained were in the extent of 44–20 nm. The energy gap of NF1 was noticed to be improved between 3.05 eV and 2.11 eV with calcium doping. Agglomerated coalescence and recombination of electron-hole pairs were observed from HR- SEM and PL spectroscopy respectively. RhB dye degradation performance, mechanism and kinetics of prepared Ca doped Ni ferrite has been studied in detail. The efficiency of photocatalyst increased with doping. The PCD efficiency for NCF5 is 99.69% compared to NF1 which is mainly because of active parting along with prohibition of photo electron-hole pair recombination. Graphical abstract: Image, graphical abstract